Do orthopaedic and neurosciences inpatients who are at risk of falls have best practice fall prevention strategies implemented during their acute inpatient hospitalization?. (21st November 2019) - Tse, Cynthia; Esler, Victoria; Hewitt, Lyndel; Davidson, Edward
Abstract: Objective: To determine whether inpatients identified as being at high risk for falls received fall prevention interventions as recommended in the Best Practice Guidelines for Australian Hospitals. Methods: This cross‐sectional study examined medical record data from a convenience sample of inpatients admitted to orthopaedic and neurosciences wards (N = 100). Data were compared to the fall prevention recommendations. Percentages were used to describe compliance and independent samples t‐tests to assess difference in adherence. Results: Data revealed that 45% and 62% of recommendations were implemented amongst inpatients on orthopaedic and neurosciences ward, respectively ( P  < 0.001). There was a significant positive correlation between orthopaedic inpatients at higher risk of falls and those with a greater length of stay [ r (39) = .46, P  = 0.003]. When analysed together, patients who were admitted following a fall had a lower percentage of fall prevention strategies implemented ( P  < 0.001). Conclusion: Implementation of fall prevention strategies is essential to target in the inpatient setting.